Simulation of Water Level Control in a Tank Using Fuzzy Logic in Matlab. (International Journal of Engineering and Computer Science, 2017)
With the increasing troubles of indecision, imprecision and ambiguity during the modeling of various control system, the fuzzy logic plays the vital role in it. This paper presents a detailed description of simulation of water level control in a tank using fuzzy logic, which clears that fuzzy logic is an different way to represent linguistic and subjective attributes of the real world. In order to improve the efficiency and simplicity of the design process, fuzzy logic can be applied to simulation of water level control in a tank using MATLAB.This paper design a simulation system of fuzzy logic controller for water tank level control by using Fuzzy Logic Toolbox MATLAB.. This proves that fuzzy logic do a fairly good job than other controlling systems